2008
DOI: 10.1016/j.jvs.2007.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of left internal jugular phlebectasia

Abstract: Jugular vein phlebectasia, a fusiform dilatation of a vein without tortuosity, is a rare cause of cervical neck swelling in children. It commonly presents as a soft cystic mass in the neck that transiently appears during straining. Because of its rarity, jugular vein phlebectasia cases have frequently been misdiagnosed or have been managed inappropriately. This report describes the case of a left-sided internal jugular phlebectasia in a 4-year-old child that was surgically treated with a resection and an end-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The importance of a size increase with Valsalva during examinations is underscored by the fact that the majority of differential diagnoses can be ruled out if absent, leaving phlebectasias, laryngoceles and superior mediastinal cyst[ 4 ]. The most common of these, laryngocele, can be ruled out with laryngoscopy, whereas mediastinal cysts can be ruled out with CT scan[ 5 ]. Although our patient’s diagnosis was easily identified with CT and confirmed with triplex ultrasound, it was not performed with these particular suggestions in mind.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of a size increase with Valsalva during examinations is underscored by the fact that the majority of differential diagnoses can be ruled out if absent, leaving phlebectasias, laryngoceles and superior mediastinal cyst[ 4 ]. The most common of these, laryngocele, can be ruled out with laryngoscopy, whereas mediastinal cysts can be ruled out with CT scan[ 5 ]. Although our patient’s diagnosis was easily identified with CT and confirmed with triplex ultrasound, it was not performed with these particular suggestions in mind.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Lubianca-Neto et al[ 2 ] these lesions have historically been described as “congenital venous cyst, venous pseudoaneurysm, venous ectasia, venous aneurysm, venous cyst, venoma, and internal jugular phlebectasia” in the literature, with an average age of under 10 and over 60% under age 40[ 3 , 4 ]. They most commonly occur on the right side, however may be bilateral in as many as 10% of cases[ 5 , 6 ]. These aneurysms classically present as unilateral, asymptomatic, soft, compressible neck swellings that enlarge with Valsalva[ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Although most jugular vein phlebectasias are asymptomatic, some children have complained of slight discomfort during deglutition, hoarseness in phonation, and a feeling of a cervical foreign body. 11 Most cases of IJV phlebectasia are unilateral, with the right side being aff ected more oft en than the left by a ratio of approximately 5:1. 5,6,8,12 It has been suggested that the anatomic relationship of the right IJV to the cupula of the lung and the head of the clavicle may lead to a transient compression of the vein when the lung is infl ated.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous articles have mentioned the CSAs of pediatric IJP patients determined during the VM . Jeon et al reported that the CSAs of the IJV in three pediatric IJP patients averaged about 300 mm 2 , and a second study reported that, in a 4‐year‐old girl with IJP, the IJV was 20 mm in the transverse direction and 30 mm along the longitudinal axis during the VM; thus, the CSA was about 470 mm 2 . Because of the limited number of references allowed in letters to the editor, I cannot present more IJP patients; however, from these previously reported results, it appears that a CSA cutoff value of 220 mm 2 or higher is appropriate for diagnosis of IJP.…”
mentioning
confidence: 99%